Host–Guest-Induced Electron Transfer Triggers Radical-Cation Catalysis - Spicer, Rebecca L; Stergiou, Athanasios D; Young, Tom A; Duarte, Fernanda; Symes, Mark D; Lusby, Paul J (Journal of the American Chemical Society, 2020)
Modifying the reactivity of substrates by encapsulation is a fundamental principle of capsule catalysis. Here we show an alternative strategy, wherein catalytic activation of otherwise inactive quinone “co-factors” by a simple Pd2L4 capsule promotes a range of bulk-phase, radical-cation cycloadditions. Solution electron-transfer experiments and cyclic voltammetry show that the cage anodically shifts the redox potential of the encapsulated quinone by a significant 1 V. Moreover, the capsule also protects the reduced semiquinone from protonation, thus transforming the role of quinones from stoichiometric oxidants into catalytic single-electron acceptors. We envisage that the host–guest-induced release of an “electron hole” will translate to various forms of non-encapsulated catalysis that involve other difficult-to-handle, highly reactive species.